Creativity and visuality of closed spaces: the case of Ettore Scola - Martinelli, Dario (Creativity Studies, 2022)
The article seeks to discuss a particular stylistic tendency, within audiovisuality, to contextualize narration and themes within closed (and often small) places – a tendency which has been given the name of claustrophilia. While particularly suitable to genres like horrors and thrillers, where the closed space often takes sinister and threatening connotations, claustrophilia may also appear in a more positive light, as a metaphor of shelter and safety, and has been in fact represented in all kind of ways. Within this picture, and throughout all its history, Italian cinema has often shown a remarkable attention for claustrophiliac representations. As a consequence, the focus of the article will be the director Ettore Scola, a figure specialized in this approach, and particularly the case study of his 1977 release A Special Day (in Italian: Una giornata particolare), one of his most celebrated works, and a well-known one at international level, due also to its Academy Awards candidature and Golden Globe Awards win.